English-language media discourse in the era of digitalisation: Special mission and functional potential - Alla V. Guslyakova; Nina I. Guslyakova; Nailya G. Valeeva; Irina V. Vashunina (Universitas Syiah Kuala, 2023)
The article addresses the problem of the functional potential of the present-day English-language media discourse and its role in English-speaking societies and other countries where English does not have official national status. The purpose of the research is to holistically understand key functions that the English language media discourse is performing in the 21st century. The theoretical framework of this study includes mutually influencing and complementary research doctrines of Halliday's systemic functional approach, Stuart Hall's cultural studies approach, and the pragmatic approach of Jeff Verschuren. The findings are based on qualitative and quantitative analyses of scientific works dedicated to the English-language media discourse and a massive media discourse corpus of leading English-language print and online media resources. Overall, the research has proved that the English-language media discourse may perform seven key pragmatic functions (political and economic function, educational function, environmental protection and sustainable development function, integration function, innovative function, cultural diplomacy function, and the social function of sport), which help promote a 'missionary' world of democracy and sustainability, affordable education and breakthrough innovations, multiculturalism, national identity and race-free ideology, healthy sport and well-being. Moreover, it is proved that modern English-language media discourse acts as a single holistic information management system whose goal is to become a global influencer and mediator navigating between English-speaking nations and non-English world communities.